Psiworld 2015 Proceedings 2016
DOI: 10.15303/rjeap.2016.si1.a14
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits as Predictors of Aggressive Violations on the Road. Driving Experience as a Moderator

Abstract: The present study attempts to understand which personality factors predict aggressive violation on the road. We hypothesized that the relation between personality factors and aggressive violation will be moderated by driving experience. A total of 219 young drivers completed measures of personality factors and aggressive violation in traffic. The results emphasized the importance of honesty, emotionality, agreeability, conscientiousness, and openness as negative predictors of aggressive violation. Moreover, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The effect of 'openness to experience' on ethical behavior received little interest in previous studies. Findings show significant and non-significant relationships between this personality trait and ethical judgment and behavior (Havârneanu and Măirean 2016;Kalshoven, Den Hartog and De Hoogh 2011;Karim, Zamzuri and Nor 2009). In this line of thought, Havârneanu and Măirean (2016) showed that individuals who present a high level of openness to experience are likely to report a low level of aggressive violation.…”
Section: Personality Traitsmentioning
confidence: 88%
“…The effect of 'openness to experience' on ethical behavior received little interest in previous studies. Findings show significant and non-significant relationships between this personality trait and ethical judgment and behavior (Havârneanu and Măirean 2016;Kalshoven, Den Hartog and De Hoogh 2011;Karim, Zamzuri and Nor 2009). In this line of thought, Havârneanu and Măirean (2016) showed that individuals who present a high level of openness to experience are likely to report a low level of aggressive violation.…”
Section: Personality Traitsmentioning
confidence: 88%